NOTES ON A PHILOSOPHY OF ART IN JOHN DEWEY: Art as a model of experiences (Revista Apotheke, 2021)
This article presents briefly the conception of John Dewey of Art that is present in the book “Art as Experience”. Here, art is understood as a complete and pure experience model. In addition, a relationship is drawn between the understanding of art as alive and the conceptual differentiation developed by the philosopher between works of art and products of art. The present analysis has the purpose of drawing attention of the diverse readers to this conceptual division and the new way of conceiving the philosophy of art from the Dewey’s point of view.
Keywords: art, experience, museums, works of art, products of art; art; experience; museums; works of art; products of art